Analisis Strategi Bussines Model Canvas pada PT XYZ (Jurnal Manajemen Kreatif dan Inovasi, 2025)
The company, which provides outsourcing services in various sectors such as cleaning services, security, administration, and others, primarily employs the canvassing method as its main market penetration strategy. This study uses a descriptive qualitative approach with data collection techniques through unstructured interviews and observation, aiming to analyze the Business Model Canvas (BMC) strategy. The results indicate that PT XYZ has implemented the nine elements of the BMC in an integrated manner, ranging from customer segmentation, value proposition, and communication channels to cost structure. The company targets customers from mid-to-large scale industries and government institutions.